Molecular marker based estimates of genetic distance and prediction of heterosis in rice (Oryza sativa) - KUMAR, AMIT; SINGH, VIKRAM JEET; S, GOPALA KRISHNAN; BHOWMICK, PROLAY K; VINOD, K K; SETH, RAKESH; NAGARAJAN, M; ELLUR, R K; BOLLINEDI, HARITHA; SINGH, ASHOK KUMAR (The Indian Journal of Agricultural Sciences, 2020)
The association of parental divergence based on simple sequence repeats (SSR) markers and heterosis in 96 rice (Oryza sativa L) hybrids was investigated for yield and component traits under four environments. Hybrids were derived from four cytoplasmic male sterile (CMS) lines and 24 iso-cytoplasmic restorers (ICR). The genetic distance (GD) and heterosis were significantly correlated for the number of productive tillers per plant (0.537) and panicle length (0.386) in Delhi under early sowing. Under late sowing, negative correlations were also observed (-0.435, -0.401) with pollen fertility percentage. The GD and heterotic performance of hybrids were significantly correlated for panicle length (r=0.35) and number of effective tillers per plant (r=0.51). At Karnal, significant association between GD and hybrid grain yield (0.615) was observed. Besides, insignificant correlations were observed for some other traits at different locations. The non-significant correlations indicated the need of employing trait related functional/ gene based markers as well as using more abundant markers for accurately predicting the hybrid performance.